LA MEDULOTRANSFUSION EN DIVERSAS HEMOPATIAS - SANCHEZ YLLADES; CASTILLO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
Liver catalase was used to liberate O2 from H2O2 in a Warburg apparatus at 30[degree]C Excess H2O2 was always present Various compounds inhibited the evolution of O2, reading being taken at 3 min intervals for 15 min KCn at 344 X 10-14 M had little
REV MEX MED
Keywords: MEDULOTRANSFUSION, HEMOPATIAS; CIENCIAS MEDICAS; MEDICINA INTERNA; HEMATOLOGIA